HIDUP HARMONI DALAM KERAGAMAN KEYAKINAN AGAMA: PERSPEKTIF PENGHAYAT KEPERCAYAAN - Engkus Ruswana (LIPI Press, 2022)
The problem of intolerance and radicalization since the reformation era has continued to grow and is increasingly worrying, due to the opening of wide spaces for groups carrying radicalism to develop themselves, as a consequence of the widespread implementation of democracy in Indonesia. The spread of intolerance and radicalism is increasingly widespread and has infiltrated various government institutions, the police and the military, and has even infiltrated educational institutions from PAUD (Early Childhood Education) to university levels. Therefore, to overcome the increasingly serious problem of national and state harmony, it is necessary to make strong efforts from all parties to revive religious moderation and live in harmony in differences in religious beliefs, as has been applied for a long time in the life of the ancestors of the Nusantara since ancient civilizations. This paper aims to reveal that Indonesia actually has the potential of the nation's local wisdom system and values ​​with genetics of moderation and harmony in religious life, not just a concept, but has been implemented since thousands of years ago, and the method used is in the form of literature studies and expressions of results. The author's thoughts and studies are based on experience in living social and national life as citizens who believe outside of mainstream religion. Some things that need to be discussed are related to the relationship between the natural environment (habitat) and the character of the human inhabitants.